First-Principles Insight Into Au-Doped MoS2 for Sensing C2H6 and C2H4 - Qian, Guochao; Peng, Qingjun; Zou, Dexu; Wang, Shan; Yan, Bing; Zhou, Qu (Frontiers in Materials, 2020)
C2H6 and C2H4 gases are two typical decompositions produced by partial discharge of transformer oil. To fully evaluate the feasibility of MoS2-based materials for the detection of C2H6 and C2H4 gases, the adsorption of C2H6 and C2H4 molecules on intrinsic and Au-doped MoS2 monolayer have been studied in this paper by the First-principle of Density Functional Theory (DFT). The adsorption mechanism of MoS2-based monolayer were investigated carefully in terms of adsorption energy, adsorption distance, bandgap structure, charge transfer and density of states (DOS). The calculated results show that the adsorption structures of the C2H6 and C2H4 molecules on Au-doped MoS2 monolayer with larger adsorption energies were stable, and have shorter adsorption distance, higher charge transfer and stronger orbital hybridization compared with the corresponding MoS2 monolayer adsorption structures. It is concluded that the doped-Au atom affects the electronic structure of MoS2 monolayer to enhance the adsorption capacity. From this aspect, the present research offers a theoretical guidance to the application of Au-doped MoS2 materials as the sensing material for C2H6 and C2H4 gases.